Blynk activated solar panel shiner using ESP32 as microcontroller / Mohamad Imran Noor Hisam - Noor Hisam, Mohamad Imran (2024)
In its simplest form, solar energy is the act of using photovoltaic panels (PV) to either directly or indirectly transform solar energy into electrical power. Actually, the majority of the energy that humans can utilize on Earth comes from clean, green power. Solar energy holds the key to the future of power generation because of its ecologically beneficial nature. It's become well recognized as a practical instrument all throughout the world. A lot of research is being done to maximize the power that sunlight can provide, but some major obstacles to doing so are dust accumulation on solar panels and air pollution, which can reduce the energy output of solar cells by more than 25% and 40% in some parts of the world, including tropical nations like India. Periodic cleaning is necessary to maintain the proper operation of the solar energy production process, which is generated from the solar panels. Therefore, in this field, solutions like automatic cleaners are significantly needed to simplify, reduce time, and save manpower. This paper's primary goal is to develop a smart solar panel cleaner that can autonomously clean PV panel surfaces with water spray and a brush to ensure that any dirt is eliminated. In order to guarantee that the interior cleaning task is completed correctly, the ESP32 microcontroller in this system moves other parts like the dc motor and ultrasonic sensor. The intended system can now transmit data from input to output thanks to the usage of an ESP32 microcontroller. In this project, a whole prototype system is created, and its functionality is assessed